Foam, protective material, and method for producing foam

JP2025033241APending Publication Date: 2025-03-13DM NOVAFOAM +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023138816
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、エチレン分解性に優れる新規な発泡体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033241000002
    Figure 2025033241000002
  • Figure 2025033241000001
    Figure 2025033241000001
Patent Text Reader

Abstract

To provide a new form which is excellent in ethylene decomposition property.SOLUTION: A foam of a resin composition contains inorganic particles and a thermoplastic resin. The inorganic particles have ethylene gas decomposition property, and have such a structure that part of the inorganic particles are exposed from the surface of the foam.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to foams, protective materials, and methods for making foams. [Background technology]

[0002] Fresh foods such as vegetables and fruits generate ethylene gas through their own physiological functions, which accelerates ripening and deterioration. This causes the problem that fresh foods have a short shelf life from production, transportation, and sale until consumption.

[0003] Known methods for solving this problem include a method of adsorbing ethylene gas and a method of decomposing ethylene gas.

[0004] For example, Patent Document 1 discloses a sheet-like functional film that is made of plastic and capable of attaching ethylene to its surface, and that contains, or has applied or vapor-deposited on its surface, a substance having a catalytic function that can decompose ethylene into carbon dioxide and water and / or release the ethylene from one side of the functional film to the other side, at least on the order of ppm or ppb. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 135433 Summary of the Invention [Problem to be solved by the invention]

[0006] A main object of the present disclosure is to provide a novel foam having excellent ethylene decomposition property. [Means for solving the problem]

[0007] The inventors of the present disclosure have conducted extensive research to solve the above-mentioned problems, and have found that a foam exhibits excellent ethylene decomposition ability by forming the foam from a resin composition containing inorganic particles and a thermoplastic resin, using inorganic particles having ethylene gas decomposition ability as the inorganic particles, and further by forming the foam into a structure in which the inorganic particles are partly exposed from the surface of the foam.

[0008] The present disclosure has been completed based on these findings and through further investigations. That is, the present disclosure provides the inventions of the following aspects.

[0009] Item 1. A foam of a resin composition containing inorganic particles and a thermoplastic resin, The inorganic particles have an ethylene gas decomposition property, A foam having a structure in which a portion of the inorganic particles is exposed from a surface of the foam. Item 2. The foam according to item 1, wherein the inorganic particles protrude from a surface of the foam. Item 3. The foam according to Item 1 or 2, wherein the inorganic particles are at least one type selected from the group consisting of zinc oxide, platinum, titanium oxide, magnesium oxide, and calcium oxide. Item 4. The foam according to any one of Items 1 to 3, wherein the inorganic particles have a particle size of 50 μm or less. Item 5. The foam according to any one of Items 1 to 4, wherein the thermoplastic resin includes at least one selected from the group consisting of olefin-based resins, styrene-based resins, vinyl chloride-based resins, vinyl acetate-based resins, polyvinyl alcohol-based resins, acrylic-based resins, polyacetal-based resins, polyester-based resins, polycarbonate resins, polyamide-based resins, and thermoplastic elastomers. Item 6. The foam according to any one of Items 1 to 5, wherein the content of the inorganic particles in the foam is 0.01% by mass or more. Item 7. The foam according to any one of Items 1 to 6, wherein a mass ratio of the thermoplastic resin to the inorganic particles is 0.1 to 10.0 parts by mass of the inorganic particles per 100 parts by mass of the thermoplastic resin. Item 8. The foam according to any one of Items 1 to 7, wherein the foam has an expansion ratio of 3 or more. Item 9. The foam according to any one of Items 1 to 8, which is in the form of a rod, a sheet, a mesh, a bag, a cylinder, a box, or a cocoon ball. Item 10. A protective material comprising the foam according to any one of items 1 to 9. Item 11. The protective material according to Item 10, wherein the protective material is a food protective material. Item 12. A method for producing a foam according to any one of items 1 to 9, comprising: A method for producing a foam, comprising foaming a resin composition containing the inorganic particles and the thermoplastic resin. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a novel foam having excellent ethylene decomposition property.

[0011] The foam of the present disclosure utilizes the ethylene decomposition action of inorganic particles, and therefore has the advantage that the ethylene decomposition ability is less likely to decrease compared to methods that utilize ethylene adsorbents that physically adsorb ethylene.

[0012] In addition, since the packaging body of the present disclosure contains ethylene-decomposable inorganic particles in the foam, it is expected that, for example, by using the foam as a protective material for food, the food that has been transported and sold together with the protective material will be stored in a refrigerator or the like by the consumer, and the foam will exert an effect of decomposing ethylene gas in the refrigerator, leading to a reduction in food waste. In other words, the foam of the present disclosure can be effectively used in all aspects of food production, transportation, sales, and consumption.

[0013] In addition, the foam of the present disclosure also exhibits a function of cushioning impacts applied to food, and therefore can exhibit an effect of suppressing deterioration, spoilage, etc. caused by damage to food. For example, if the foam of the present disclosure is made into a mesh shape, moisture generated during ethylene decomposition can efficiently evaporate from the foam, and an effect of suppressing retention of moisture can be exhibited.

[0014] Furthermore, by using ethylene-decomposing inorganic particles having antibacterial properties, it is possible to inhibit food spoilage caused by bacteria. [Brief description of the drawings]

[0015] [Figure 1] 1 is an electron microscope image (magnification: 5000 times) of the foam obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1. Foam The foam of the present disclosure is a foam of a resin composition containing inorganic particles and a thermoplastic resin, the inorganic particles having ethylene gas decomposition properties, and a structure in which the inorganic particles are partially exposed from the surface of the foam. Since the foam of the present disclosure has such a structure, it can exhibit excellent ethylene decomposition properties and can be suitably used, for example, as a food protection material. The foam of the present disclosure will be described in detail below.

[0017] In the numerical ranges described in the present disclosure in stages, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In addition, the upper limit and the upper limit, the upper limit and the lower limit, or the lower limit and the lower limit described separately may be combined to form a numerical range. In addition, in the numerical ranges described in the present disclosure, the upper limit or the lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0018] Additionally, each feature disclosed herein may be combined with any other feature disclosed herein.

[0019] The foam of the present disclosure is a foam of a resin composition containing inorganic particles and a thermoplastic resin.

[0020] (thermoplastic resin) Examples of the thermoplastic resin include olefin resins, styrene resins, vinyl chloride resins, vinyl acetate resins, polyvinyl alcohol resins, acrylic resins, polyacetal resins, polyester resins, polycarbonate resins, polyamide resins, and thermoplastic elastomers containing the constituent components of these resins. These thermoplastic resins may be used alone or in combination of two or more kinds.

[0021] Of these, olefin-based resins, styrene-based resins, and thermoplastic elastomers (e.g., olefin-based thermoplastic elastomers, styrene-based thermoplastic elastomers, etc.) are preferred, and it is particularly preferred to contain at least an olefin-based resin because they have excellent mechanical properties such as flexibility and elasticity.

[0022] The olefin resin is usually a poly C2-3 olefin resin such as a polyethylene resin or a polypropylene resin, with a polyethylene resin being preferred.

[0023] Examples of polyethylene resins include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-propylene copolymer, ethylene-butene-1 copolymer, ethylene-propylene-butene-1 copolymer, ethylene-(4-methylpentene-1) copolymer, ethylene-vinyl acetate copolymer (EVA resin), and ethylene-methyl methacrylate copolymer. These polyethylene resins can be used alone or in combination of two or more. Among these polyethylene resins, LDPE, LLDPE, EVA resin, and the like are preferred from the viewpoint of foamability and the like.

[0024] The number average molecular weight of the polyethylene resin may be, for example, about 10,000 to 300,000, preferably about 15,000 to 200,000, and more preferably about 20,000 to 100,000. The molecular weight is measured by gel permeation chromatography (GPC) at a measurement temperature of 140° C., using orthodichlorobenzene as a solvent and a column (Shodex GPCAD-806MS), and by universal calibration using polystyrene as a standard.

[0025] The melt flow rate (MFR) of the polyethylene resin may be 0.1 g / 10 min or more, for example, 0.1 to 60 g / 10 min, preferably 0.2 to 25 g / 10 min, more preferably 0.25 to 8 g / 10 min, and most preferably 0.3 to 5 g / 10 min, according to a method in accordance with JIS K7210 (190°C, load 21.2 N). If the MFR is too large, the foamability and strength may decrease, and conversely, if it is too small, the foamability may decrease. It is generally known that as the MFR increases, the melt tension decreases, making the foam more likely to break, but by adjusting the lower limit of the MFR to the above range, the foamability can be improved.

[0026] The melting point or softening point of the polyethylene resin is, for example, about 80 to 150°C, preferably about 90 to 140°C, and more preferably about 100 to 130°C.

[0027] The thermoplastic resin containing an olefin-based resin may be an olefin-based resin alone, or may be a combination of an olefin-based resin and another thermoplastic resin (for example, a styrene-based resin such as polystyrene).

[0028] The weight ratio of the olefin resin to the other thermoplastic resin can be selected from the range of about olefin resin / other thermoplastic resin=100 / 0 to 10 / 90 (for example, 100 / 0 to 50 / 50), and when both resins are combined, it is about olefin resin / other thermoplastic resin=99 / 1 to 30 / 70, preferably 98 / 2 to 50 / 50, and more preferably 95 / 5 to 70 / 30 (particularly 93 / 7 to 80 / 20). If the ratio of the olefin resin is too low, there is a risk of reduced foamability.

[0029] The content of thermoplastic resin in the foam of the present disclosure (i.e., in the resin composition constituting the foam of the present disclosure) is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and is preferably 99% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less; preferred ranges include about 50 to 99% by mass, about 50 to 80% by mass, about 50 to 70% by mass, about 80 to 99% by mass, and about 90 to 99% by mass.

[0030] (Inorganic particles) The inorganic particles have an ethylene gas decomposition property. In the present disclosure, the ethylene gas decomposition property of the inorganic particles specifically means a property of promoting a reaction that produces water and carbon dioxide by contacting the inorganic particles with ethylene gas in the presence of oxygen gas (oxidation reaction of ethylene gas by a metal oxide).

[0031] The type of inorganic particles having ethylene gas decomposition properties (hereinafter, sometimes referred to as ethylene gas decomposable inorganic particles) is not particularly limited as long as the effects of the invention of the present disclosure are exhibited, and examples thereof include zinc oxide, platinum, titanium oxide, magnesium oxide, and calcium oxide. The ethylene gas decomposable inorganic particles contained in the foam of the present disclosure may be of only one type or of two or more types. Among these, from the viewpoint of suitably exhibiting the effects of the invention of the present disclosure, it is preferable that the ethylene gas decomposable inorganic particles contain zinc oxide. Zinc oxide is an oxide of zinc represented by the chemical formula ZnO.

[0032] From the viewpoint of suitably exerting the effects of the present invention, the particle size of the inorganic particles in the foam is preferably 50 μm or less, more preferably 10 μm or less, and even more preferably 1 μm or less, and is preferably 0.01 μm or more, more preferably 0.02 μm or more, and even more preferably 0.03 μm or more. Preferred ranges include about 0.01 to 50 μm, about 0.01 to 10 μm, about 0.01 to 1 μm, about 0.02 to 50 μm, about 0.02 to 10 μm, about 0.02 to 1 μm, about 0.03 to 50 μm, about 0.03 to 10 μm, and about 0.03 to 1 μm.

[0033] The content of ethylene gas decomposable inorganic particles in the foam of the present disclosure (i.e., in the resin composition constituting the foam of the present disclosure) is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and even more preferably 0.03 mass% or more, and is preferably 10.0 mass% or less, more preferably 8.0 mass% or less, and even more preferably 7.0 mass% or less. Preferred ranges include about 0.01 to 10.0 mass%, about 0.01 to 8.0 mass%, about 0.01 to 7.0 mass%, about 0.02 to 10.0 mass%, about 0.02 to 8.0 mass%, about 0.02 to 7.0 mass%, about 0.03 to 10.0 mass%, about 0.03 to 8.0 mass%, and about 0.03 to 7.0 mass%.

[0034] The mass ratio of the thermoplastic resin to the ethylene-decomposable inorganic particles in the foam of the present disclosure (i.e., in the resin composition constituting the foam of the present disclosure) is preferably about 0.1 to 10.0 parts by mass, more preferably about 0.2 to 5.0 parts by mass, and even more preferably about 0.3 to 3.0 parts by mass of the ethylene-decomposable inorganic particles per 100 parts by mass of the thermoplastic resin.

[0035] The foam of the present disclosure has a structure in which a part of the ethylene decomposable inorganic particles is exposed from the surface of the foam. Since the foam of the present disclosure is a foam of a resin composition, the surface area is large, and the ethylene decomposable inorganic particles are exposed on the surface of such a foam. Therefore, the surface area of ​​the ethylene decomposable inorganic particles on the surface of the foam of the present disclosure is also large, and it is considered that the foam as a whole exhibits excellent ethylene decomposition properties.

[0036] From the viewpoint of more suitably exerting the effect of the present disclosure, it is preferable that the ethylene decomposable inorganic particles protrude from the surface of the foam.In this case, it is not necessary that all of the ethylene decomposable inorganic particles exposed on the surface of the foam protrude from the surface of the foam, and as long as at least a part of the ethylene decomposable inorganic particles protrude from the surface of the foam, the effect of enhancing ethylene decomposition can be improved.In addition, the protrusion of the ethylene decomposable inorganic particles from the surface of the foam is a part of the ethylene decomposable inorganic particles, and the part that does not protrude is buried in the foam.

[0037] (foaming agent) The foam of the present disclosure is obtained by foaming a resin composition (expandable resin composition) containing a thermoplastic resin and ethylene-decomposable inorganic particles, and the resin composition may contain a foaming agent. Note that in the production process of the foam of the present disclosure, the foaming agent is contained in the resin composition, and after the foam is formed, the foaming agent volatilizes and may not be contained in the foam.

[0038] The foaming agent may be a conventional foaming agent or a decomposable foaming agent (chemical foaming agent), but a volatile foaming agent (physical foaming agent) is preferred because it can improve the foaming ratio by a simple method. Examples of the volatile foaming agent include inorganic foaming agents (nitrogen, carbon dioxide, oxygen, air, water, etc.) and organic foaming agents (aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, chlorinated hydrocarbons, fluorinated hydrocarbons, alcohols, ethers, aldehydes, ketones, etc.). Among these, lower aliphatic hydrocarbons such as butane (n-butane, isobutane) and pentane (n-pentane, isopentane, etc.) are widely used because they are inexpensive and have low toxicity.

[0039] The ratio of the foaming agent in the resin composition is, for example, about 0.01 to 30 parts by mass, preferably about 0.1 to 25 parts by mass, and more preferably about 1 to 20 parts by mass (particularly about 5 to 15 parts by mass) relative to 100 parts by mass of the thermoplastic resin.

[0040] (Foam nucleating agent) The foam of the present disclosure may further contain a foam nucleating agent. Examples of foam nucleating agents include silicon compounds (talc, silica, zeolite, etc.), inorganic acid salts (carbonates or bicarbonates such as sodium bicarbonate, calcium carbonate, magnesium carbonate, sodium hydrogen carbonate, and ammonium carbonate), organic acids or their salts (citric acid, sodium citrate, calcium stearate, aluminum stearate, zinc stearate, etc.), metal oxides (zinc oxide, titanium oxide, aluminum oxide, etc.), and metal hydroxides (aluminum hydroxide, etc.). These foam nucleating agents may be used alone or in combination of two or more.

[0041] The ratio of the foam nucleating agent in the foam of the present disclosure is, for example, about 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass (particularly 0.5 to 2 parts by mass) relative to 100 parts by mass of the thermoplastic resin.

[0042] (Surfactant) The foam of the present disclosure may further contain a surfactant. Examples of the surfactant include fatty acid esters (esters of C8-24 fatty acids and polyhydric alcohols, such as palmitic acid monoglyceride, triglyceride stearic acid monoglyceride, triglyceride stearic acid, etc.), fatty acid amides (C8-24 fatty acid amides, such as palmitic acid amide, stearic acid amide, etc.). These surfactants may be used alone or in combination.

[0043] The proportion of the surfactant in the foam of the present disclosure is, for example, about 0.01 to 30 parts by mass, preferably 0.05 to 20 parts by mass, and more preferably 0.1 to 10 parts by mass (particularly 1 to 5 parts by mass) relative to 100 parts by mass of the thermoplastic resin.

[0044] (Other additives) The foam of the present disclosure may further contain conventional additives as other additives. Conventional additives include colorants (dyes, pigments, etc.), surface smoothing agents, cell regulators, stabilizers (antioxidants, heat stabilizers, UV absorbers, etc.), viscosity regulators, compatibilizers, dispersants, antistatic agents, antiblocking agents, antifogging agents, fillers (calcium carbonate, carbon fibers, etc.), lubricants, release agents, lubricants, impact modifiers, plasticizers, flame retardants, biocides (bactericides, bacteriostatic agents, antifungal agents, preservatives, insect repellents, etc.), and deodorants. These conventional additives can be used alone or in combination of two or more.

[0045] The ratio of other additives in the foam of the present disclosure is, for example, 50 parts by mass or less, preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of the thermoplastic resin.

[0046] (Flame retardant) Examples of flame retardants include phosphate esters and other phosphorus compounds such as ammonium polyphosphate, ethylene bis tris (2-cyanoethyl) phosphonium chloride, tris (tribromophenyl) phosphate, tris (tribromophenyl) phosphate, and tris (3-hydroxypropyl) phosphine oxide, chlorine-based flame retardants such as chlorinated paraffin, chlorinated polyolefin, and perchlorocyclopentadecane, bromine-based flame retardants such as hexabromobenzene, ethylene bis dibromonorbornane dicarboxyimide, ethylene bis tetrabromophthalimide, tetrabromobisphenol A derivatives, tetrabromobisphenol S, and tetrabromodipentaerythritol, and mixtures thereof. Flame retardants can be used alone or in combination of two or more.

[0047] (UV absorber) Examples of the ultraviolet absorbing agent include benzotriazole-based agents, benzophenone-based agents, salicylic acid-based agents, acrylate-based agents, etc. The ultraviolet absorbing agents may be used alone or in combination of two or more kinds.

[0048] (Coloring agent) Examples of the pigment include inorganic pigments (titanium oxide, iron oxide, chromium oxide, cadmium sulfide, etc.) and organic pigments (azo lake type, thioindigo type, phthalocyanine type, anthraquinone type). Examples of the dye include azo type, anthraquinone type, triphenylmethane type, etc. The colorant can be used alone or in combination of two or more types. The amount of the pigment and dye to be added is not particularly limited and may be the ratio of the other additives described above, but is preferably 5 parts by mass or less, more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the resin composition of the present invention.

[0049] (Antistatic agent addition proposal) Examples of the antistatic agent include the above-mentioned surfactants, fatty acid esters, and polymeric antistatic agents. Examples of the fatty acid esters include esters of stearic acid and oleic acid, and examples of the polymeric antistatic agents include polyether ester amides. The antistatic agents can be used alone or in combination.

[0050] (Foam characteristics) The expansion ratio of the foam of the present disclosure may be 3 times or more (e.g., 3 to 90 times), for example, about 3.1 to 85 times, preferably 3.5 to 80 times, and more preferably 4.0 to 75 times (particularly 20 to 70 times). In the present disclosure, even though inorganic particles are contained, a high expansion ratio is also possible, for example, an expansion ratio of 10 times or more (particularly 20 times or more) is also possible, for example, about 10 to 90 times, preferably 20 to 85 times, and more preferably 30 to 75 times (particularly 35 to 70 times). If the expansion ratio is too low, there is a risk of reduced flexibility.

[0051] The foam of the present disclosure preferably contains at least a closed cell structure, and the open cell ratio, which is the ratio of open cells to the total number of cells (the sum of open cells and closed cells), may be 90% by volume or less, for example, 0.1 to 90% by volume, preferably 1 to 80% by volume (for example, 2 to 70% by volume), and more preferably 3 to 50% by volume (particularly 5 to 40% by volume). If the open cell ratio is too high, the mechanical properties of the foam may be deteriorated. On the other hand, in applications requiring flexibility, the foam may have a high open cell ratio, for example, a foam with an open cell ratio of 20% by volume or more, preferably 30% by volume or more, and more preferably more than 50% by volume. The open cell ratio may be adjusted, for example, by changing the composition of the resin components other than the master batch.

[0052] The average cell diameter of the foam of the present disclosure is, for example, about 0.3 to 2 mm, preferably about 0.4 to 1.5 mm, and more preferably about 0.5 to 1.3 mm (particularly about 0.6 to 1 mm). If the average cell diameter is too small, it may be difficult to increase the expansion ratio, and if it is too large, the mechanical properties may be reduced.

[0053] The foam of the present disclosure preferably has a skin layer on the surface, and the coverage of the skin layer with respect to the entire surface may be 60 area% or more (particularly 80 area% or more), preferably 90 area% or more, or may be 100 area% (the entire surface is the skin layer). The skin layer means a non-foamed layer that extends with a substantially uniform thickness on the surface of the foam.

[0054] The average thickness of the skin layer can be selected from the range of about 0.001 to 1 mm, and is, for example, about 0.005 to 0.1 mm, preferably about 0.008 to 0.05 mm, and more preferably about 0.01 to 0.03 mm (particularly about 0.012 to 0.025 mm).

[0055] The ethylene decomposition rate of the foam of the present disclosure is preferably 5% or more, more preferably 10% or more, and further preferably 20% or more, with the upper limit being, for example, 100% or less.

[0056] Furthermore, in the present disclosure, by using ethylene decomposable inorganic particles having antibacterial properties, it is possible to suppress food spoilage caused by bacteria, etc. For example, since zinc oxide has antibacterial properties, by using zinc oxide as the ethylene decomposable inorganic particles, the foam of the present disclosure can also exhibit antibacterial properties.

[0057] The antibacterial properties of the foam of the present disclosure are evaluated in accordance with the provisions of JIS Z 2801:2012, and are preferably 2.0 or more, more preferably 2.5 or more. An antibacterial activity value of 2.0 or more is considered to have antibacterial performance. A higher antibacterial activity value is preferable because it indicates a higher antibacterial effect, and the upper limit is not particularly limited. The antibacterial activity value preferably satisfies the above conditions against various bacteria, and more preferably satisfies the above conditions against both Staphylococcus aureus and Escherichia coli.

[0058] In this specification and claims, the expansion ratio, open cell ratio, average cell diameter, average skin layer thickness, ethylene decomposition property, and antibacterial property are each measured by the methods described in the Examples below.

[0059] The shape of the package of the present disclosure is not particularly limited and can be appropriately selected depending on the application. Specific examples of the shape of the package of the present disclosure include a rod shape, a sheet shape, a mesh shape, a bag shape, a cylinder shape, a box shape, a cocoon shape, and the like.

[0060] The packages of the present disclosure are useful, for example, as food protectants.

[0061] As described above, the foam of the present disclosure utilizes the ethylene decomposition action of inorganic particles, and therefore has the advantage that the ethylene decomposition ability is less likely to decrease compared to a method that utilizes an ethylene adsorbent that physically adsorbs ethylene.

[0062] In addition, since the packaging body of the present disclosure contains ethylene-decomposable inorganic particles in the foam, it is expected that, for example, by using the foam as a protective material for food, the food that has been transported and sold together with the protective material will be stored in a refrigerator or the like by the consumer, and the foam will exert an effect of decomposing ethylene gas in the refrigerator, leading to a reduction in food waste. In other words, the foam of the present disclosure can be effectively used in all aspects of food production, transportation, sales, and consumption.

[0063] In addition, the foam of the present disclosure also exhibits a function of cushioning impacts applied to food, and therefore can exhibit an effect of suppressing deterioration, spoilage, etc. caused by damage to food. For example, if the foam of the present disclosure is made into a mesh shape, moisture generated during ethylene decomposition can efficiently evaporate from the foam, and an effect of suppressing retention of moisture can be exhibited.

[0064] [Method of manufacturing foam] The method for producing a foam of the present disclosure may be a method for foam-molding a resin composition containing a thermoplastic resin and ethylene-decomposable inorganic particles, and a conventional method may be used as a method for foaming the resin composition. The foam-molding method is usually a method of melt-kneading a resin composition and foam-molding it.

[0065] The melt kneading may be performed using a conventional melt kneader, such as a single screw or vented twin screw extruder, etc. Prior to the melt kneading, the thermoplastic resin, the ethylene decomposable inorganic particles, and other components (foaming agent and, if necessary, foaming nucleating agent, additives, etc.) may be premixed using a conventional method, such as a mixer (a tumbler, a V-type blender, a Henschel mixer, a Nauta mixer, a ribbon mixer, a mechanochemical device, an extrusion mixer, etc.).

[0066] As the foam molding method, a conventional method such as extrusion molding (e.g., T-die method, inflation method, etc.), injection molding, etc. can be used. Among these, extrusion molding is preferred because it can produce foams having strong magnetic force and high expandability with high productivity.

[0067] In the extrusion molding method, for example, a single screw extruder (e.g., a vented extruder) or a twin screw extruder (e.g., a co-rotating twin screw extruder or a counter-rotating twin screw extruder) can be used as the extruder. A multi-stage extruder such as a tandem extruder is preferred because it allows easy adjustment of the foaming conditions and can achieve a high foaming ratio.

[0068] In the extrusion molding method, the method of introducing the foaming agent is not particularly limited, and a decomposable foaming agent (chemical foaming agent) may be blended in advance with the foamable resin composition. However, it is preferable to introduce a volatile foaming agent (physical foaming agent) in the extruder, since this is a simple method that can improve the expansion ratio.

[0069] The shape of the nozzle is not particularly limited and can be selected according to the application of the foam (for example, when the foam is used as a protective material, the shape of the object (or article) to be protected). For example, the shape may be one-dimensional, such as a rod or string, two-dimensional, such as a sheet, film, or two-dimensional mesh (net), or three-dimensional, such as a block, plate, column, slit, L-shape, U-shape, pipe, or ring. The sheet foam may have at least one flat or uneven surface, or one surface may be uneven and the other surface may be uneven. In the case of a long sheet foam, this uneven surface is often formed along the longitudinal direction. By forming an uneven surface, the slippage of the object to be protected can be suppressed and the cushioning effect can be enhanced. The height of the uneven portion is not particularly limited.

[0070] The extrusion-foamed foam may be cooled by a conventional method, for example, a cooling method using a cooler. In the cooling method using a cooler, the cooling medium may be compressed air, water (cooling water), air (blower), etc. Examples of the cooling method include a method of injecting compressed air, a method of cooling with a blower, a method of cooling by spraying water, a method of cooling using a cooling jacket, etc. The temperature of the cooling medium may be, for example, 0 to 60°C, preferably 5 to 55°C, and more preferably about 10 to 50°C.

[0071] In the method of injecting compressed air, the air pressure may be, for example, about 0.1 to 10 MPa, preferably about 0.2 to 5 MPa, and more preferably about 0.3 to 1 MPa. The amount of compressed air injected may be, for example, about 100 to 1000 liters / minute, preferably about 200 to 500 liters / minute, and more preferably about 250 to 400 liters / minute.

[0072] If necessary, the obtained foam (particularly, a sheet-like foam) may be subjected to secondary processing [for example, thermoforming such as vacuum forming, pressure forming, vacuum pressure forming, and match mold forming (for example, thermoforming using a mold)].

[0073] The foam molding or secondary molding temperature may be, for example, about 70 to 300°C, preferably about 80 to 280°C, and more preferably about 85 to 260°C.

[0074] The shape of the foam can be appropriately selected depending on the application, and may be, for example, a one-dimensional shape such as a rod or a string; a two-dimensional shape such as a sheet, a film or a two-dimensional mesh (net); or a three-dimensional shape such as a mesh, bag, cylinder, box, cocoon, block, plate, column, slit, L-shape, U-shape, pipe or ring. EXAMPLES

[0075] The present disclosure will be described in more detail below with reference to examples and comparative examples, but each configuration and their combinations in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited by the embodiments, but is limited only by the scope of the claims.

[0076] [Raw materials] LDPE: Low-density polyethylene (Novatec, manufactured by Japan Polyethylene Corporation) Ethylene decomposable inorganic particles: Zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd.) Average particle size: 0.28 μm Blowing agent: Isobutane (commercially available) Foaming nucleating agent: Talc ("Microace K-1" manufactured by Nippon Talc Co., Ltd.) Average particle size: 7.4 μm Surfactant: Monoglyceride stearate (commercial product)

[0077] [Expansion ratio] The expansion ratio was calculated based on the following formula. Expansion ratio (times)=density of resin composition for foam / apparent density of foam.

[0078] [Open cell ratio] The foam weight was measured in advance, and the foam was placed in water and then left under reduced pressure of -400 mmHg for 1 minute to allow water to penetrate into the open cell structure. The pressure was returned to atmospheric pressure from the reduced pressure state, and the water adhering to the foam surface was removed and the weight was measured, and then the weight was calculated using the following formula (1).

[0079] Open cell ratio (%) = {(w2-w1) / d3} / (w1 / d1-w1 / d2) (1) (In the formula, w2 is the weight of the foam after absorbing water, w1 is the weight of the foam before absorbing water, d1 is the apparent density of the foam, d2 is the apparent density of the resin composition used in the foam, and d3 is the density of water at the time of measurement.)

[0080] [Average bubble diameter (cell size)] The cross section of the foam was observed with a scanning electron microscope or a digital microscope (Scalar Corporation), and the cell diameters in the TD and MD directions were measured at 10 random locations, and the average was taken as the cell diameter. Each cell diameter was taken as the average (mm) of the major axis and minor axis.

[0081] [Average Skin Thickness] Using a digital microscope (Scalar Corporation) and filing & 2D measurement software ("AR-CNVMF" manufactured by Artray Corporation), the thickness of the skin layer in the TD direction was measured at 10 random locations, and the average value was taken as the average thickness of the skin layer (mm).

[0082] [Ethylene decomposition] The ethylene decomposition property of the foam was evaluated by the following procedure. The results are shown in Table 1. 10 g of the foam obtained in the examples and comparative examples was placed in a 5-liter Tedlar bag, and 3 liters of ethylene gas with an initial concentration of 100 ppm was poured in. The ethylene gas concentration in the bag was measured using a gas detector tube at regular intervals to evaluate the decomposition property of ethylene gas by the foam. The evaluation criteria for ethylene decomposition were as follows: a sample in which an ethylene concentration reduction rate of 20% or more was confirmed within 48 hours was rated "A", a sample in which an ethylene concentration reduction rate of 15% or more but less than 20% was rated "B", and a sample in which an ethylene concentration reduction rate of less than 15% was rated "C".

[0083] [Antibacterial] The antibacterial properties of the foam were evaluated according to the method specified in JIS Z 2801:2012, using the following procedure. The results are shown in Table 1.

[0084] (Preparation of press sheet for measurement) A predetermined amount of each resin composition was filled into a SUS mold. The heating plate was set to 200°C, and a hydraulic heat press (PEWR-30 manufactured by Kansai Roll Co., Ltd.) was used to preheat for 7 minutes and pressurize for 2 minutes at a gauge pressure of 10 MPa. The mixture was then transferred to a cooling plate set to 20°C, compressed at a gauge pressure of 10 MPa, and cooled for 3 minutes to produce a 2 mm thick press sheet for measurement.

[0085] (Antibacterial Test) Test pieces were prepared by punching out a 2 mm thick test sheet prepared according to the method described above in "Preparation of test sheet". Next, in accordance with JIS Z2801 (film coating method), the test pieces were inoculated with a bacterial solution of Staphylococcus aureus NBRC 12732 and Escherichia coli NBRC 3972, and incubated for 24 hours in an atmosphere with a temperature of 35°C and a relative humidity of 90% or more. The criteria for antibacterial properties are as follows: A: Antibacterial activity value is 2.0 or higher. C: Antibacterial activity value is less than 2.0.

[0086] [Foam manufacturing] <Masterbatch manufacturing> 80 parts by mass of LDPE and 20 parts by mass of ethylene-decomposable inorganic particles were charged into a ball mill and mixed while rotating for 10 minutes, and then the resulting mixture was continuously charged from a hopper into a KRC kneader (manufactured by Kurimoto Iron Works, Ltd.) to melt and knead it, and the resin composition that was continuously discharged was cooled with water and then cut with a pelletizer to prepare a master batch. <Example 1> 90 parts by mass of LDPE, 2.5 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were put into an extruder, 8.0 parts by mass of isobutane gas was injected from the middle of the extruder, and then the extruder was cooled to a temperature suitable for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The obtained foam was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 100 mm and a wall thickness (thickness) of 2.0 mm, and had a basis weight of 55.7 g / m2, an expansion ratio of 33 times, an open cell ratio of 2.2%, an average cell diameter of 0.93 mm, and an average thickness of the skin layer of 0.028 mm.

[0087] <Example 2> 90 parts by mass of LDPE, 5.0 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were put into an extruder, 8.0 parts by mass of isobutane gas was injected from the middle of the extruder, and then the extruder was cooled to a temperature suitable for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The obtained foam was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet. Specifically, it was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 104 mm, a cylindrical wall thickness (thickness) of 2.1 mm, a basis weight of 60.4 g / m2, an expansion ratio of 32 times, an open cell ratio of 2.1%, an average cell diameter of 0.93 mm, and an average thickness of the skin layer of 0.023 mm.

[0088] <Example 3> 90 parts by mass of LDPE, 7.5 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were put into an extruder, 8.0 parts by mass of isobutane gas was injected from the middle of the extruder, and then the extruder was cooled to an appropriate temperature for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The obtained foam was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet. It was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 103 mm and a cylindrical wall thickness (thickness) of 2.0 mm, and had a basis weight of 54.1 g / m2, an expansion ratio of 34 times, an open cell ratio of 2.4%, an average cell diameter of 0.75 mm, and an average thickness of the skin layer of 0.027 mm.

[0089] <Example 4> 90 parts by mass of LDPE, 10.0 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were put into an extruder, 8.0 parts by mass of isobutane gas was injected from the middle of the extruder, and then the extruder was cooled to a temperature suitable for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The obtained foam was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet. It was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 100 mm and a cylindrical wall thickness (thickness) of 2.1 mm, and had a basis weight of 96.6 g / m2, an expansion ratio of 20 times, an open cell ratio of 2.9%, an average cell diameter of 0.69 mm, and an average thickness of the skin layer of 0.024 mm.

[0090] <Example 5> 95 parts by mass of LDPE, 5.0 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were fed into an extruder, 2.0 parts by mass of isobutane gas was injected midway through the extruder, and the extruder was cooled to an appropriate temperature for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The foam obtained was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 104 mm, a cylindrical wall thickness (thickness) of 1.0 mm, and a basis weight of 187.7 g / m 2 The foaming ratio was 4.9 times, the open cell ratio was 3.2%, the average cell diameter was 0.86 mm, and the average thickness of the skin layer was 0.024 mm.

[0091] <Example 6> 60 parts by mass of LDPE, 20 parts by mass of PS, 10.0 parts by mass of master batch, 1.0 part by mass of foaming nucleating agent, and 3.0 parts by mass of surfactant were fed into an extruder, 22.0 parts by mass of isobutane gas was injected midway through the extruder, and the extruder was cooled to an appropriate temperature for foaming and extruded from a circular nozzle attached to the tip to obtain a foam. The foam obtained was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 106 mm, a cylindrical wall thickness (thickness) of 2.6 mm, and a basis weight of 36.0 g / m 2 The foaming ratio was 70 times, the open cell ratio was 1.9%, the average cell diameter was 1.18 mm, and the average thickness of the skin layer was 0.021 mm.

[0092] <Comparative Example 1> 100 parts by mass of the master batch, 1.0 parts by mass of the foaming nucleating agent, and 3.0 parts by mass of the surfactant were put into an extruder, 8.0 parts by mass of isobutane gas was injected from the middle of the extruder, and then the extruder was cooled to a temperature suitable for foaming, and extruded from a circular nozzle attached to the tip to obtain a foam. The obtained foam was a cylindrical sheet with an average diameter of approximately circular cross section of about 100 mm. Specifically, it was a cylindrical sheet with an average diameter of approximately circular cross section (cylinder width) of 100 mm and a cylindrical wall thickness (thickness) of 2.2 mm, and had a basis weight of 65.3 g / m2, an expansion ratio of 31 times, an open cell ratio of 2.2%, an average cell diameter of 0.95 mm, and an average thickness of the skin layer of 0.025 mm.

[0093] <Observation of foam surface using an electron microscope> The surface condition of the foam was confirmed by SEM images using a scanning electron microscope (SEM (SU1510: Hitachi)) and an EDX analyzer (EDAX APEX). The magnification of the SEM images was adjusted in the range of 50 times to 10,000 times to obtain multiple SEM images (for example, SEM images at 50 times, 200 times, 1000 times, 2000 times, 5000 times, and 10,000 times, respectively). In addition, as a pretreatment for observation, the cross section of the foam was cut out with a cutter and platinum-coated before SEM observation. From each SEM image, the exposed and protruding state of the inorganic particles from the foam surface was confirmed, and the particle size of the inorganic particles was measured. The results are shown in Table 1.

[0094] When the electron microscope images of the foams obtained in Examples 1 to 6 were examined, zinc oxide was exposed on the surface of the foam, and furthermore, zinc oxide protruded from the foam surface. An electron microscope image (magnification 5000 times) of the foam obtained in Example 2 is shown in Figure 1. It can be seen that zinc oxide was exposed on the surface of the foam, and furthermore, zinc oxide (particles 1, 2, 3, 4) protruded from the foam surface.

[0095] [Table 1]

Claims

1. A foam of a resin composition containing inorganic particles and a thermoplastic resin, The inorganic particles have an ethylene gas decomposition property, A foam having a structure in which a portion of the inorganic particles is exposed from a surface of the foam.

2. The foam of claim 1 , wherein the inorganic particles protrude from a surface of the foam.

3. The foam according to claim 1 or 2, wherein the inorganic particles are at least one selected from the group consisting of zinc oxide, platinum, titanium oxide, magnesium oxide, and calcium oxide.

4. The foam according to claim 1 or 2, wherein the inorganic particles have a particle size of 50 μm or less.

5. 3. The foam according to claim 1, wherein the thermoplastic resin comprises at least one selected from the group consisting of olefin-based resins, styrene-based resins, vinyl chloride-based resins, vinyl acetate-based resins, polyvinyl alcohol-based resins, acrylic-based resins, polyacetal-based resins, polyester-based resins, polycarbonate resins, polyamide-based resins, and thermoplastic elastomers.

6. The foam according to claim 1 , wherein the content of the inorganic particles in the foam is 0.01% by mass or more.

7. 3. The foam according to claim 1, wherein a mass ratio of the thermoplastic resin to the inorganic particles is 0.1 to 10.0 parts by mass of the inorganic particles per 100 parts by mass of the thermoplastic resin.

8. The foam according to claim 1 or 2, wherein the foam has an expansion ratio of 3 times or more.

9. The foam according to claim 1 or 2, which is in the form of a rod, a sheet, a mesh, a bag, a cylinder, a box, or a cocoon ball.

10. A protective material comprising the foam according to claim 1 or 2.

11. The protective material of claim 10, wherein the protective material is a food protective material.

12. A method for producing the foam according to claim 1 or 2, comprising the steps of: A method for producing a foam, comprising foaming a resin composition containing the inorganic particles and the thermoplastic resin.

Citation Information

Patent Citations

  • Functional film, functional container, and method for retaining freshness

    WO2017135433A1